Using Kolb’s Experiential Learning to Educate Nursing Students About Providing Culturally and Linguistically Appropriate Care - Krol, Maria; Adimando, Andrea (Nursing Education Perspectives, 2021)
Over the past decade, the Agency for Healthcare Research and Quality and The Joint Commission have identified that communication problems are a root cause of most serious adverse events and that patients with limited English proficiency are more likely than others to suffer physical harm when such errors occur. It is essential to educate nursing students on the challenges of patients with limited English proficiency and empower them with tools, such as the National Culturally and Linguistically Appropriate Services standards, to minimize this phenomenon in their future nursing practice. We describe an educational intervention designed to accomplish this using Kolb’s experiential learning theory as a foundation for implementation.
0 citations (Crossref) [2023-10-31]
Keywords: Humans; Nursing; Problem-Based Learning; Students; article; dept.nur; experiential learning; human; limited English proficiency; nursing student; peer-reviewed; problem based learning; transcultural care